Current Diagnosis of Alzheimer’s Disease (Revista de Medicina Clinica, 2018)
Dementia is defined as the acquired impairment of cognitive abilities that hinder the satisfactory performance of daily activities. We perform this paper in order to establish a guide for dementia diagnosis. Specifically, we analyzed Alzheimer’s disease the main cause of dementia, especially in people over 65 years of age, representing 60% of cases. We review the diagnostic criteria of the DSM V and ICD-10, as well as the most recently criteria (Dubois and NIA-AA), and the anatomical and functional image diagnosis with CT, MRI , PET and brain SPECT. Finally, we conducted a review of the most used biomarkers in CSF and plasma for the early diagnosis of this disease.
Keywords: Dementi; Alzheimer Disease; Mild Cognitive Deficit